Peningkatan Keterampilan Menulis Karangan Narasi Melalui Model Pembelajaran Circuit Learning Di Sekolah Dasar - Ningsih, Ritawati (Faculty Of Education, 2024)
This research was motivated by students' low skills in writing narrative essays. One solution to overcome this problem is through the circuit learning model. The aim of this research is to describe the improvement in the ability to write narrative essays through the circuit learning model in class V students at UPT SD Negeri 042 Sungai Agung. This research is Classroom Action Research (PTK) which was carried out in two cycles. Each cycle consists of two meetings and four stages, namely planning, implementation, observation and reflection. The research subjects were 22 students in class V UPT SD Negeri 042 Sungai Agung. Data collection techniques include observation, tests and documentation. Based on the research results, pre-action students' narrative essay writing skills were 69.45, in cycle I it increased to 74.44 and in cycle II the students' average score was 83.4. The increase in the percentage of students who achieved the KKM in writing narrative essays in the pre-action condition was 32%, cycle I was 68%, and cycle II increased to 82%. Thus, it can be concluded that through the circuit learning model, learning can improve the narrative essay writing skills of class V UPT SD Negeri 042 Sungai Agung students.